16S rRNA genes- and metagenome-based confirmation of syntrophic butyrate-oxidizing methanogenesis enriched in high butyrate loading. (February 2022) - Meng, Xianghui; Cao, Qin; Sun, Yong; Huang, Siyuan; Liu, Xiaofeng; Li, Dong
Graphical abstract: Highlights: Enrichment of better butyrate-tolerated and highly efficient syntrophic consortia. Microbial community became more stable since BAL of 1.6 g/(L·d). The syntrophic consortia included SBOB, SAOB, methanogen and IHT bacteria. Metagenome revealed the enhancement of IHT and methanogenesis pathways. New butyric degradation pathway might produce propionate and methyl compounds. Abstract: The understanding and enrichment of consortia formed by syntrophic butyrate-oxidizing bacteria and methanogens in the complex environment are crucial for effectively degrading butyrate and preventing acid inhibition. In this study, the better butyrate-tolerated and highly efficient microbial consortia were domesticated and enriched through adding butyric acid ranging from 0.2 to 4.4 g/(L·d). The volumetric biogas production continuously increased to 1.65 L/(L·d). Microbial community diversity showed that a dramatic shift of bacterial structure occurred at BAL of 1.6 g/(L·d) and the structure presented better stability at high BAL. The syntrophic consortia and the main metabolic pathways were revealed through combination of the 16S rDNA and metagenome sequencing analyses. Syntrophomonas was the major butyrate-oxidizing bacterium and oxidized butyrate mainly through β-oxidaiton. Synergistaceae and Mesotoga acted as the main acetate-oxidizing bacteria. IHT and methanogenesis pathways were strongly enhanced by DMER64 and Methanosarcina as the main H2 carrier and dominant methanogen, respectively.